2017
DOI: 10.3768/rtipress.2017.op.0042.1709
|View full text |Cite
|
Sign up to set email alerts
|

Financing Long-Term Services and Supports: Continuity and Change

Abstract: This PDF document was made available from www.rti.org as a public service of RTI International. More information about RTI Press can be found at http://www.rti.org/rtipress. RTI International is an independent, nonprofit research organization dedicated to improving the human condition by turning knowledge into practice. The RTI Press mission is to disseminate information about RTI research, analytic tools, and technical expertise to a national and international audience. RTI Press publications are peerreviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In contrast, we examine changes that respondents experience in the 2-year period during which Medicaid entry occurs. To the best of our knowledge, only one other study has used linked survey and administrative data to examine Medicaid entry (Wiener et al, 2013); unlike our study, it focuses on respondent traits measured before entry (rather than changes in respondent circumstances), and it uses data prior to the expansion of partial Medicaid under the Medicare Improvements for Patients and Providers Act (MIPPA) of 2008.…”
Section: New Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we examine changes that respondents experience in the 2-year period during which Medicaid entry occurs. To the best of our knowledge, only one other study has used linked survey and administrative data to examine Medicaid entry (Wiener et al, 2013); unlike our study, it focuses on respondent traits measured before entry (rather than changes in respondent circumstances), and it uses data prior to the expansion of partial Medicaid under the Medicare Improvements for Patients and Providers Act (MIPPA) of 2008.…”
Section: New Contributionsmentioning
confidence: 99%
“…Prior studies have found that Medicaid entry is positively associated with Black race, Hispanic ethnicity, low levels of education, worse health status, and being unmarried (Tavares et al, 2020;Wiener et al, 2013) as well as prior high OOP medical spending, the lack of supplementary health insurance (Willink et al, 2016), trouble paying for medical bills (Willink et al, 2019), prior health care use (Borck et al, 2014;Keohane et al, 2017Keohane et al, , 2018Lim et al, 2014;Stockwell et al, 2012), and some state and federal policies (Keohane et al, 2016(Keohane et al, , 2019. Although these studies provide valuable information on Medicaid entry, many use Medicare claims data only and, as a result, are not able to measure income and assets.…”
Section: Introductionmentioning
confidence: 99%
“…Over recent decades, US long-term care policy has undergone a major shift toward home-and community-based services. 59,60 Still, access to these services remains limited and varies widely from state to state. [61][62][63] To investigate how these structural factors shape caregivers' health, we used an ecosocial theoretical framework, 64 longitudinal data from the Medical Expenditures Panel Survey (MEPS), and individual-level difference-in-difference models to assess the relationship between onset of Medicaid home care and family caregivers' health.…”
Section: Introductionmentioning
confidence: 99%
“…Only Medicaid-the means-tested public health insurance program-provides long-term home care services in the US; Medicare, the universal health insurance program for people aged 65 years or older or with disabilities, provides just limited, short-term services. 59,62,[65][66][67] We focused on publicly funded long-term care, rather than privatepaid care, because such programs can reduce caregivers' physical and emotional burden without increasing their financial burden. 65,[68][69][70][71] Little research has investigated how publicly funded home care affects caregivers, and existing studies do not assess caregiver health outcomes, are from outside the US, or compare home care to institutionalization rather than to continued stand-alone family caregiving.…”
Section: Introductionmentioning
confidence: 99%
“…Medicaid is the predominant payor for NHs, covering approximately 63% of long-term residents (i.e., residents in NHs for over 100 days; Harris-Kojetin et al, 2016), whereas Medicare provides skilled nursing facility (SNF) coverage—up to 100 days—mainly for post-acute rehabilitative NH care. As of 2014, over 95% of U.S. NHs served long-term residents covered by Medicaid and short-term SNF residents (Centers for Medicare & Medicaid Services [CMS], 2015; Wiener et al, 2017).…”
Section: Introductionmentioning
confidence: 99%